(untitled) (SCIENCE TIME JOURNAL, 2024)
This article explores the stylistic features of phraseological dialectisms in the English language. Phraseological dialectisms are expressions and idiomatic phrases that are unique to specific dialects or regional variations of English. The study aims to uncover the distinctive characteristics of these linguistic phenomena, shedding light on their role in reflecting cultural identity, preserving linguistic diversity, and enriching the expressive possibilities within different dialect communities. The research draws on various sources, including linguistic studies, cultural analyses, and anecdotal evidence, to provide insights into the semantic, syntactic, phonetic, and pragmatic aspects of phraseological dialectisms. The findings highlight the significance of these expressions in oral traditions, storytelling, the arts, and the negotiation of identity within a specific dialect community. By understanding the stylistic features of phraseological dialectisms, we gain a deeper appreciation of the intricate relationship between language, culture, and regional identity in the English-speaking world.